Computer simulation of beam dynamics on JINR phasotron up to 660 MeV energy - Onischenko, L.M.; Samsonov, E.V. (Вопросы атомной науки и техники, 2006)
Project of increasing the beam intensity of the 660 MeV JINR Proton Phasotron by an external injection of the H - beam with energy 5 MeV is now under design. Process of the beam injection was investigated formerly. Investigation of the acceleration process up to the final energy is reported in this paper. It is found that the beam losses exist along the acceleration. Проект увеличения интенсивности пучка протонного Фазотрона ОИЯИ на энергию 660 МэВ с помощью внешней инжекции H - ионов с энергией 5 МэВ находится в стадии разработки. Процесс инжекции пучка был исследован ранее. В настоящее время проводятся исследования ускорения пучка до конечной энергии. Обнаружено, что потери пучка существуют вдоль всего цикла ускорения. Проект збільшення інтенсивності пучка протонного фазотрона ОІЯД на енергію 660 МеВ за допомогою зовнішньої інжекції H - іонів з енергією 5 МеВ перебуває в стадії розробки. Процес інжекції пучка був досліджений раніше. Зараз проводяться дослідження прискорення пучка до кінцевої енергії. Виявлено, що втрати пучка існують уздовж усього циклу прискорення.